LB746. Safety and Immunogenicity of a Booster Dose of Novavax COVID-19 Vaccine, Adjuvanted (NVX-CoV2373) in Adults from the PREVENT-19 Trial in the United States. (15th December 2022) - Áñez, Germán; Dunkle, Lisa M; Gay, Cynthia L; Kotloff, Karen L; Patel, Nita; Plested, Joyce S; McGarry, Alice; Woo, Wayne; Cai, Rongman; Cho, Iksung
Abstract: Background: Novavax COVID-19 Vaccine, Adjuvanted (5 µg recombinant spike protein/50 µg Matrix-M TM adjuvant; NVX-CoV2373) has received regulatory authorizations for use in adults ≥ 18 years globally. Methods: Participants from PREVENT-19 (NCT04611802), a phase 3, randomized, observer-blinded, placebo-controlled trial that evaluated the efficacy, safety, and immunogenicity of a primary series of 2 doses of NVX-CoV2373 given 21 days apart, in adults ≥ 18 years in the United States and Mexico, were eligible to receive a booster dose at least 6 months after the initial vaccination series. Short-term safety and immunogenicity of the booster dose was assessed in an ad hoc analysis of 298 participants. Results: There was an incremental increase compared to the initial vaccination series in local and systemic reactogenicity, which was transient and mostly mild-to-moderate in intensity. Most unsolicited adverse events were also mild-to-moderate in severity; there were no deaths or treatment-related SAEs and 2/298 booster recipients in this analysis reported unrelated SAEs. Neutralizing, anti-S IgG, and hACE2 receptor binding inhibiting antibodies against the ancestral (Wuhan) strain 28 days after booster were higher than those 14 days after primary vaccination (Table). Overall, humoral responses were high regardless of interval between priming and booster vaccination, but a longer interval yielded stronger responses. Higher immune responses against the Omicron BA.1, BA.2, and BA.5 variants were also observed after the booster dose than after the primary series in a subset of 14-18 participants tested. Overall, humoral responses were high and broad regardless of age after any vaccination, but higher responses were observed in adults < 65 years after initial and booster vaccinations. A booster dose induced more robust antibody responses compared with the primary series in adults ≥ 65 years. Conclusion: A single booster dose of NVX-CoV2373 demonstrated a satisfactory safety profile, and high levels of neutralizing, anti-S IgG, and hACE2 inhibition antibody responses against the SARS-CoV-2 prototype Wuhan as well as against the Omicron variant including recently emerged sub-variants. Disclosures: Germán Áñez, MD, Novavax Inc.: employer|Novavax Inc.: Stocks/Bonds Lisa M. Dunkle, MD, Novavax, Inc: Employee|Novavax, Inc: Stocks/Bonds Nita Patel, MS, CRP, Novavax, Inc.: employer|Novavax, Inc.: Stocks/Bonds Joyce S. Plested, PhD, Novavax Inc.: employer|Novavax Inc.: Stocks/Bonds|Novavax Inc.: Stocks/Bonds Alice McGarry, MPH, Novavax: Employee|Novavax: Stocks/Bonds Wayne Woo, MS, Novavax: Employee|Novavax: Stocks/Bonds Rongman Cai, PhD, Novavax Inc.: employer|Novavax Inc.: Stocks/Bonds Iksung Cho, MS, Novavax, Inc.: employer|Novavax, Inc.: Stocks/Bonds.